Pembentukan Karakter Anak Usia Dini Melalui Budaya Sekolah - Yuliana Ngewi; Efrida Ita; Karolina Ngora; Sesantris Elkana Nio; Agustina Dhone; Kristiana Owa Kaju; Maria Bergita Bhoko; Florentina Dasilva Bhoko; Yuliana Dhoso; Apolonia Kue; Febronia Yasinta Wea; Maria Susanty Moi; Maria Emmanuela Lebo; Ludfika Claudia Owa (Jurnal Inovasi Pendidikan Dan Pembelajaran, 2026)
This study was motivated by the importance of school culture in shaping early childhood character, while several challenges were still found, including limited facilities and infrastructure, incosistent student discipline, suboptimal character habituation, and school enviromental conditions that still require improvement. The purpose of this study was to analyze the role of school culture in shaping early childhood character in four early childhood education institutions located in Ngada and Nagekeo Regencies, namely TKK Negeri Wue, TKK Obor Desa Ladolima, Kober Santo Yoseph Freinnademetz, and TKK Santo Aloysius Ulubelu. This research employed a descriptive qualitiative approach. Data were collected through observation, interviews, and documentation. Data analysis was conducted through data reducation, data display and conclusion drawing, using source and to enscure data validity. The findings revealed that the scool cultures implemented in the four institutions inclued the 3S (smile, greeting, and salutation), the use of school uniforms, cleanliness habits, maintaining clasroom order and clamness, effective use of learning time, flag ceremonies or other activites promoting national values, and various character buliding habituation activites. The consistent implementation of these school culture practices contributed to the development of children’s character, particulary in terms of discipline, responsibility, cooperation, piolitenss, and enivormental awareness. In addition, school culture fostered a positive social emotional climated through warm interactions between teachers and children, routine habituation activites, and teacher’s role modeling in daily life. Although each institution faced different challenges, school culture remained an effective means of instilling positive character values in early childhood.